Atopic Dermatitis: Natural History, Diagnosis, and Treatment. (2nd April 2014) - Thomsen, Simon Francis
Abstract : Atopic dermatitis is an inflammatory skin disease with early onset and with a lifetime prevalence of approximately 20%. The aetiology of atopic dermatitis is unknown, but the recent discovery of filaggrin mutations holds promise that the progression of atopic dermatitis to asthma in later childhood may be halted. Atopic dermatitis is not always easily manageable and every physician should be familiar with the fundamental aspects of treatment. This paper gives an overview of the natural history, clinical features, and treatment of atopic dermatitis.